STUDENTS’ PERCEPTION TOWARD TEACHER OF ENGLISH IN TEACHING PERFORMANCE - Nyayu Yayu Suryani (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
The teaching performance of the teacher plays important roles in improving the students’ achievement in learning English. However, the performance of the teacher in teaching English is judged by the students’ performance. Therefore, the main purpose of this study was to find out the students’ perception about the teacher of English in teaching performance at SMA N 14 Palembang related to the questionnaire given. The population of this research was all the third year students of SMA Negeri 14 Palembang. They were 48 students taken as a sample. A descriptive method was used in this research. The data were obtained by means of a questionnaire. Based on the result of the data analysis, the students’ perception of their teacher’s performance in teaching covered seven aspects were as follows: (a)How the teacher open the lesson, (b) The attitude of the teacher in learning process, (c) The teacher material mastery, (d) Teaching and learning process, (e) The use of media, (f) Evaluation, and (g) How the teacher close the lesson. It concluded that most of the students’ perception about the teacher of English in teaching performance at SMA N 14 Palembang gave positive perception